Diversity of Naked Amoebae in Soils of Forest Areas of Zhytomyr Region (Ukraine) - Patsyuk, Marina (Zootaxa, 2020)
Here we consider the morphotypes and changing species composition of naked amoebae in soils of forest areas in Zhytomyr region (Ukraine). The species composition and morphotypes of amoebae are influenced by the microclimate of soil and litter. Complexes of naked amoebae in the study area constitute two clusters: one of broadleaf (oak) and mixed forests, another of coniferous forests. The most similar species compositions were found in soils of oak and mixed forests (64 % similarity). The least similar were amoebae complexes of coniferous forests and oak forests, and coniferous forests and mixed forests. Non-parametric multidimensional scaling (MDS) showed that species complex of amoebae of mixed forests and oak forests had moister and more acidic soils compared to coniferous forests.